UTILIZATION OF DIGITAL PUBLIC SPACE BY THE MEDAN CITY GENERAL ELECTION COMMISSION IN ORDER TO INCREASE VOTER PARTICIPATION IN THE 2024 MEDAN CITY REGIONAL ELECTIONS - Muhammad Hasbi Maulana Batubara; Tonny P. Situmorang; Bengkel Ginting (SOSIOEDUKASI, 2026)
This study aims to examine how Regional Head Election organizers utilize the digital public sphere and the obstacles faced by the General Elections Commission (KPU) in leveraging this space to increase voter participation. Employing a qualitative approach, the research was conducted in Medan City, with data collected through in-depth interviews, observation, and documentation. The results indicate that the Medan City KPU has effectively utilized the digital public sphere via various social media platforms throughout the election stages—from the preparatory phase to the post-election period. A primary objective of this social media optimization is to disseminate election-related information and encourage the public to actively exercise their voting rights. However, obstacles within the digital public sphere are inevitable; for instance, algorithms can limit the reach of content, preventing it from connecting with a wider audience. The study underscores that the successful optimization of the digital public sphere is heavily influenced by the capacity and commitment of the election organizers.